Assessing Chemical Literacy of Pre-service Chemistry Teacher: Rasch Analysis - Marfuatun Marfuatun; Nahadi Nahadi; Yuliani Galuh; Hernani Hernani (SHS Web of Conferences)
The study aimed to validate the chemical literacy (CL) test instrument for pre-service chemistry teachers (PCTs), categorize the CL- item difficulty, and evaluate PCTs’ chemical literacy levels. The participants were 49 students in the chemistry education department at Daerah Istimewa Yogyakarta. Three different scientific knowledge were employed to assess student chemical literacy. A paper-based test was carried out for the data collection. The findings revealed that the developed CL test achieved both validity and reliability in its assessments. Interestingly, while a majority of the test items were categorized as relatively easy, the students exhibited a lower-than-expected proficiency in completing the CL test.